Analisis Faktor Kejadian Stunting pada Anak Usia Balita di Puskesmas Telang Jaya Telang Kecamatan Muara Telang Kabupaten Banyuasin - Haryani Haryani; Erma Puspita Sari; Hasbiah Hasbiah; Titin Dewi Sartika (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The World Health Organization (WHO), in 2017 amounted to 150.8 million (22.2%), globally, Africa and Asia contributed the most with 39% and 55%, respectively. The prevalence of stunting is very high in Asia where almost 1 in 10 children under five is underweight than in Latin America and the Caribbean. WHO places Indonesia as the third country with the highest stunting prevalence rate in Asia in 2017. The purpose of this study was to determine the relationship between exclusive breastfeeding, low birth weight, and nutritional intake with the incidence of stunting in children under five at the Telang Jaya Telang Health Center, Muara Telang District. Banyuasin Regency in 2021. The method used in this research is an analytical survey with a cross sectional approach with data collection using questionnaires and interviews. The statistical test used is the chi-square test. The population in this study were toddlers at the Telang Jaya Telang Health Center, Muara Telang District, Banyuasin Regency in January-May 2021, totaling 3133 toddlers, and the sample size used the Slovin formula so that it used 97 respondents. Univariate analysis showed that from 97 respondents studied, there were 25 respondents (25.8%) who were stunted, 50 respondents who did not breastfeed exclusively (51.5%), LBW as many as 33 respondents (34.0%), and 45 respondents (46.4%). The results of statistical tests showed that there was a relationship between exclusive breastfeeding (p.value 0.032), low birth weight (p.value = 0.000), and nutritional intake (p.value = 0.022). The conclusion is that there is a relationship between exclusive breastfeeding, low birth weight, and nutritional intake with the incidence of stunting in children under five at the Telang Jaya Telang Health Center, Muara Telang District, Banyuasin Regency in 2021.